Polymorphism of Prolactin Gene (PRL/PstI) In Sikumbang Jonti Duck Using PCR-RFLP Methods - Teguh Rafian; Yurnalis Yurnalis; Yosi Fenita; Rafi Iskandarsyah (Jurnal Sain Peternakan Indonesia, 2022)
This study is aimed to determine polymorphism of the Prolactin gene (PRL|PstI) in Sikumbang Jonti ducks using PCR-RFLP (Polymerase Chain Reaction–Restriction Fragment Length Polymorphism) method. This study used 56 Sikumbang Jonti ducks whose blood samples were taken. Gene amplification used a pair of primers forward 5' TGC AAA CCA TAA AAG AAA AGA 3' and reverse 5' CAA TGA AAA GTG GCA AAG CAA 3', which resulted in a 400 bp fragment in exon 5 of the Prolactin (PRL) gene. The amplification product was restricted using the PstI enzyme, which recognizes the truncation site (5' G↓ACGTC 3'). From 56 samples of Sikumbang Jonti ducks identified, just one genotype was found, homozygous (-/-) with only one allele (-). Analysis of the restriction product in Sikumbang Jonti ducks obtained a uniform genetic variation of PRL|PstI (monomorphic) with an allele frequency (-) of 100%.